Assessing the Link between Zinc Levels and Obesity in Young Adults: Zinc levels and Obesity in young adults - Syed, Maria; Siddiqui, Sana; Ahmad, Sidra; Syed, Komal (Medical Journal of South Punjab, 2023)
Background: Obesity is an international health issue associated to multiple long-term medical conditions like type 2 diabetes, heart disease, and different kinds of malignancies. There is strong evidence to show that obesity and zinc deficiency may be related. The objective of the research was to find out whether obesity in younger adults was related to serum zinc levels.Materials and Methods: A cross-sectional study was carried out in Quaid-e-Azam Medical University, Bahawalpur, involving 123 young adults aged between 18 and 25 years. The study aimed to assess body weights based on BMI (Body Mass Index) and serum zinc levels. The study lasted six months from September 2022 to March 2023.Results: Serum zinc levels were significantly lower in overweight and obese younger adults compared to younger adults of normal weight. It was observed that an increase in BMI was associated with decreased serum zinc levels.Conclusion: These results suggested an association between obesity in younger adults and serum zinc levels. More research is needed in order to confirm these findings, verify the negative correlation between these two parameters and to examine the processes underlying the link between zinc and obesity.Keywords: BMI, serum zinc levels, young adults, obesity, cross-sectional study